(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
In this research work, author concentrates on the stochastically modelling of a computer system with software redundancy by introducing the concept of hardware component preventive maintenance (PM) and hardware maximum repair time (MRT). The system fails independently from normal mode. All the repair activities such as hardware repair, software up-gradation, hardware preventive maintenance before failure and hardware replacement after maximum repair time are carried out by a single server immediately on need basis. All random variables are statistically independent. The negative exponential distribution is taken for the failure time of the component while the distributions of repair time, up-gradation time, preventive maintenance and replacement time are assumed arbitrary with different probability density functions. Semi-Markov process and regenerative point technique are used for obtaining the values various performance measures. The behaviour of some important performance measure has been examined for different parameters and costs. The profit comparison of the present model has also been made with that of the model analyzed by Munday et. al (2019).